Molecular analysis of the adaptive response in Salmonella Typhimurium after starvation in salty conditions - Elabed, Hamouda; Merghni, Abderrahmen; Hamza, Rim; Bakhrouf, Amina; Gaddour, Kamel (The Journal of Infection in Developing Countries, 2016)
Introduction: The pathogenic bacterium Salmonella enterica serovar Typhimurium elicits a variety of genetic programs to adapt to stress conditions encountered within hostile environments such as host phagocytes and preserved food. Methodology: In this work, differential display (DD) methodology was used to investigate the effect of one month starvation in a salty microcosm (0.5 M NaCl) on transcript profiling in a Salmonella Typhimurium LT2 strain. cDNA fragments resulting from differentially expressed mRNA were eluted from the gel, re-amplified, cloned, and then sequenced. Results: A total of 21 differentially expressed bands were detected by DD reverse transcription-polymerase chain reaction (RT-PCR). However, only 12 of them were successfully identified as upregulated genes in stressed cells. Based on the sequencing data and BLAST analysis, these genes were sopA, ssaD, yhhK, gmK, cspC, uspA, ompR, phoP, stcC, fimA, acrA,and yehZ. As a confirmation of the differential expression, RT-PCR was carried out using a set of specific primers. Remarkably, the expression levels of these genes were significantly increased in starved bacteria compared to standard laboratory conditions. Conclusions: Our results indicate that the starvation of Salmonella Typhimurium over one month in a salty microcosm changes the expression of stress proteins, response regulator in a two-component system, outer membrane proteins, effector proteins translocated by Salmonella pathogenicity island SPI1 and SPI2 type III secretion systems (TTSS), several metabolic enzymes, efflux pumps, and transport proteins. This suggests that the expression of the identified genes is important for the response of this pathogen to starvation in salt.